Kattaikkuttu a rural theatre tradition in South India - Bruin, Hanne M. de (Forms of drama, 2023)
"This is the first book to offer a clear introduction to Kattaikkuttu (or Terukkuttu), a vibrant, vocal and physical outdoor Tamil theatre tradition. It describes the theatre's characteristic heroic nature as expressed through its principal, male kattai characters, explores its history, social status and ritual context, and examines the production of all-night plays. It traces the theatre's disentanglement from its organic embedding into the social and ritual village organization and its transition towards a more autonomous and more professional theatre form during the last 150 years, providing case studies of all-night plays, and examines more recent developments in the form"--Provided by publisher.